Structural, photoluminescent and photocatalytic properties of TiO2:Eu3+ coatings formed by plasma electrolytic oxidation - Stojadinović, Stevan; Radić, Nenad; Grbić, Boško; Maletić, Slavica; Stefanov, Plamen; Pačevski, Aleksandar; Vasilić, Rastko (Applied surface science, 2016)
•TiO2:Eu3+ coatings are formed by plasma electrolytic oxidation (PEO).•Photoluminescence is related to transitions of Eu3+ from level 5D0 to levels 7FJ.•Eu3+ ions occupy non-inversion symmetry sites in the coatings.•PEO time is an important factor affecting photocatalytic activity. In this paper, we used plasma electrolytic oxidation (PEO) of titanium in water solution containing 10g/L Na3PO4·12H2O+2g/L Eu2O3 powder for preparation of TiO2:Eu3+ coatings. The surfaces of obtained coatings exhibit a typical PEO porous structure. The energy dispersive X-ray spectroscopy analysis showed that the coatings are mainly composed of Ti, O, P, and Eu; it is observed that Eu content in the coatings increases with PEO time. The X-ray diffraction analysis indicated that the coatings are crystallized and composed of anatase and rutile TiO2 phases, with anatase being the dominant one. X-ray photoelectron spectroscopy revealed that Ti 2p spin-orbit components of TiO2:Eu3+ coatings are shifted towards higher binding energy, with respect to pure TiO2 coatings, suggesting that Eu3+ ions are incorporated into TiO2 lattice. Diffuse reflectance spectroscopy showed that TiO2:Eu3+ coatings exhibit evident red shift with respect to the pure TiO2 coatings. Photoluminescence (PL) emission spectra of TiO2:Eu3+ coatings are characterized by sharp emission bands in orange–red region ascribed to f–f transitions of Eu3+ ions from excited level 5D0 to lower levels 7FJ (J=0, 1, 2, 3, and 4). The excitation PL spectra of TiO2:Eu3+ coatings can be divided into two regions: the broad band region from 250nm to 350nm associated with charge transfer state of Eu3+ and the series of sharp peaks in the range from 350nm to 550nm corresponding to direct excitation of the Eu3+ ions. It is observed that the intensity of peaks in excitation and emission PL spectra increases with the concentration of Eu3+, but the peak positions remain practically unchanged. The ratio of PL emission for electric and magnetic dipole transitions indicates highly asymmetric environment around Eu3+ ions. The photocatalytic activity (PA) of TiO2:Eu3+ coatings is evaluated by measuring the photodegradation of methyl orange under simulated sunlight conditions. It is shown that PEO time, i.e., the amount of Eu3+ incorporated into coatings is an important factor affecting PA; TiO2:Eu3+ coating formed after 1min of PEO time showed the highest PA.